Exercise training-induced changes in inflammatory mediators and heat shock proteins in young tennis players - Ziemann, E.; Zembron-Lacny, A.; Kasperska, A.; Antosiewicz, J.; Grzywacz, T.; Garsztka, T.; Laskowski, R. (Journal of Sports Science & Medicine, 2013)
Heat shock proteins (Hsp) represent proteins' groups, whose protective function, may be induced by heat, reactive oxygen species, cytokines etc. We evaluated blood levels of Hsp27 and Hsp70, and their relation to skeletal muscle damage and inflammation in young tennis players before and after the conditioning camp. Blood samples were collected directly after tournament season, 3-day rest and 14-day conditioning camp that followed. Hydrogen peroxide (H2O2) demonstrated the highest concentration directly after tournament season, which significantly decreased at camp's end. The pro-inflammatory cytokines IL-1ß and TNFa decreased, whereas anti-inflammatory cytokines IL-6 and IL-10 increased after 3d rest and 14d camp. Hsp27 increased after 3d rest and remained so after 14d camp, while Hsp70 decreased from baseline to camp's completion. Hsp27 and Hsp70 correlated significantly with H2O2, IL-1ß and TNFa. Muscle damage, observed as creatine kinase (CK) activity changes, increased after 14d camp similarly to Hsp27 and anti-inflammatory cytokines IL-6 and IL-10. Obtained data allows to conclude that decrease of Hsp27 and increase in pro-inflammatory cytokines could be a good indicator of overreaching. Reverse tendencies in these proteins may verify accuracy of conditioning camp. Finally, this training program caused an increase in the anti-inflammatory cytokines concentrations, improving individual status of recovery.